The Role of Teachers' Emotional Intelligence in Improving Character Education of Students at SLB N Kota Jantho - Firmawati; Fuadi, Tuti Marjan; Jamaluddin; Humaira, Tasya (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2025)
This study aims to analyze the role of teachers' emotional intelligence in improving character education for students at SLB N Kota Jantho. The research method used is a qualitative method with a case study approach. Data collection was carried out through interviews, observations, and documentation. The participants in this study were the school supervisor, principal, and teachers at SLB N Kota Jantho The results of the study indicate that teachers' emotional intelligence plays an important role in improving character education for students at SLB N Kota Jantho. Teachers with high emotional intelligence are able to create a conducive learning environment, build positive relationships with students, and become role models in character development. Components of emotional intelligence, such as self-awareness, self-regulation, motivation, empathy, and social skills, have been shown to contribute significantly to the improvement of aspects of student character education, such as discipline, responsibility, honesty, and caring. The findings of this study indicate that training and development of emotional intelligence for SLB teachers needs to be a priority for schools and local governments. Investment in improving teachers' emotional intelligence can contribute to improving the quality of character education for students with special needs at SLB N Kota Jantho.